INTERPRETATION OF THE PHENOMENON OF PUBLICISTIC DISCOURSE IN LINGUISTICS - Akbarova Masuma (Social science and innovation, 2023)
This article focuses on the term discourse in mass communication, which is one of the vital issues in pragmatic and cognitive linguistics, a field that is emerging as a new trend in modern linguistics. The term “discourse” has been coined in the field of linguistics. Despite its initial understanding as a connected and accepted consequence in speech or in text, it is defined in linguistics by its interpretation as a complicated communicative event in modern linguistics.